RESTful API dengan Dukungan AES-GCM dan XChaCha20-Poly1305 dalam Pengelolaan Data Identitas Penduduk (Studi Kasus Desa Galudra) - Restu Oktafiandi; Deni Suprihadi (Universitas Kebangsaan Republik Indonesia, 2025)
The management of citizen identity data plays a critical role in governmental administration, including in Galudra Village, Cugenang District, Cianjur Regency. Traditionally, data recording has relied on Microsoft Excel, which, while adequate in the early stages, becomes inefficient as the population grows and the demand for fast, accurate, and secure services increases. This study develops a RESTful API integrated with AES-GCM and XChaCha20-Poly1305 cryptographic algorithms to enhance both security and efficiency in managing resident data. AES-GCM is employed to secure stored data, whereas XChaCha20-Poly1305 is applied to protect data during transmission. The system was developed using the waterfall model, with blackbox testing applied to validate its functionality. The implementation results indicate that the system effectively accelerates data processing and safeguards sensitive information. Network monitoring with Wireshark confirmed that all transmitted data is well-encrypted, making it inaccessible in its original form. Therefore, this solution not only addresses efficiency and security challenges at the village level but also aligns with Law Number 27 of 2022 concerning Personal Data Protection, and serves as a reference for implementing secure information technology in local government environments.